2022
DOI: 10.1002/jcsm.13099
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between metabolic dysfunction‐associated fatty liver disease and low muscle mass in an asymptomatic Korean population

Abstract: Background Metabolic (dysfunction)‐associated fatty liver disease (MAFLD) emphasizes the metabolic dysfunction in nonalcoholic fatty liver disease (NAFLD). Although the relationship between low muscle mass and NAFLD has been suggested, the effect of MAFLD on low muscle mass is yet to be investigated. In this study, we examined the relationship between MAFLD and low muscle mass in an asymptomatic Korean population. Methods Examinees who underwent FibroScan® and bioelectrical impedance analyses on the same day d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…On average, those with NAFLD had significantly higher BMI and absolute (kg) muscle mass but when adjusted for BMI the prevalence ratio of low muscle mass was significantly higher in those with NAFLD; the opposite finding was observed when adjusted for height 2 . Previous studies have also reported a higher prevalence of low muscle mass when adjusting for BMI in those with NAFLD (8.7% vs 3.6%) [ 36 ] and no differences when adjusting for height 2 [ 5 ]. This suggests that it is important to account for adiposity when evaluating the influence of NAFLD on muscle mass, especially in overweight and obese cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…On average, those with NAFLD had significantly higher BMI and absolute (kg) muscle mass but when adjusted for BMI the prevalence ratio of low muscle mass was significantly higher in those with NAFLD; the opposite finding was observed when adjusted for height 2 . Previous studies have also reported a higher prevalence of low muscle mass when adjusting for BMI in those with NAFLD (8.7% vs 3.6%) [ 36 ] and no differences when adjusting for height 2 [ 5 ]. This suggests that it is important to account for adiposity when evaluating the influence of NAFLD on muscle mass, especially in overweight and obese cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Yu et al’s study concluded that a lower appendicular skeletal muscle mass to visceral fat area ratio is linked to a higher prevalence of subtypes of metabolic associated fatty liver disease [ 38 ]. Some mechanisms could elucidate the combined impact of reduced SMM and increased VFA on NAFLD risk, including IR, impaired lipid metabolism, and low-grade inflammation [ 24 , 39 ]. Skeletal muscles serve as a site for insulin-mediated glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…According to manufacturer’s instruction, subjects were light dressed and instructed to hold the analyzer’s handles, making contact with the electrodes on each limb. They extended their limbs to prevent their arms from touching the torso, kept their thighs from making contact and maintained a still position throughout the measurement [ 24 ]. The BIA method was validated as the reliable technique for assessing body composition, showing strong correlations with measurements obtained utilizing abdominal computed tomography and dual-energy X-ray absorptiometry (DXA), including VFA and SMM [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Seo et al. revealed that, in 6414 asymptomatic Korean individuals, there was an increased risk of low muscle mass in the non‐obese MAFLD subgroup, as compared with the control subgroup 40 . Sun et al.…”
Section: Discussionmentioning
confidence: 99%
“…revealed that, in 6414 asymptomatic Korean individuals, there was an increased risk of low muscle mass in the non-obese MAFLD subgroup, as compared with the control subgroup. 40 Sun et al also performed a propensity score-matched population-based cohort study to demonstrate that sarcopenia is a significant risk factor for the onset of esophageal cancer. 41 Thus, patients with non-obese MAFLD may be related to the high ESCC recurrence rates through the number of metabolic dysfunction and sarcopenia.…”
Section: Factormentioning
confidence: 99%